Lack of correlation between ventricular late potentials and left ventricular mass in top-level male athletes - Biffi, A.; Verdile,L.; Ansalone, G.; Spataro, A.; Spada, R.; Fernando, F.; Caselli, G.; Santini, M. (Medicine & Science in Sports & Exercise, 1999)
this study showed: 1) the low rate of positive results of SAECG- (signal-averaged electrocardiogram) parameters in top-level male athletes, similar to that found in healthy sedentary subjects; and 2) the lack of correlation between left ventricular mass and overall SAECG parameters.